Fecundity of giant freshwater prawn (Macrobrachium rosenbergii) varies with the trophic status and size of the inhabitant perennial reservoirs in Sri Lanka - RG Sanuja; AU Kuragodage; UAD Jayasinghe; PLN Lakshman; KHM Ashoka Deepananda (Journal of Fisheries)
Giant freshwater prawn (GFP, Macrobrachium rosenbergii) is an important commodity in the inland fisheries of Sri Lanka, where fecundity plays a crucial role in estimating the reproductive potential of the species. The fecundity of ovigerous GFP in relation to the trophic status and area of the reservoirs was empirically determined from the GFP collected from twenty-five dry-zone perennial reservoirs across Sri Lanka. Morphometric parameters, total and relative fecundity, and egg characteristics of ovigerous females were calculated. The total fecundity of GFP, which ranged between 5277±2069 – 29366±2371, differed significantly (p<0.05) with the trophic status and size of the reservoirs. The highest total fecundity was observed in the 24–25 cm and 185–210 g length and weight classes of GFP. The GFP inhabiting eutrophic medium perennial reservoirs exhibited the highest fecundity. Fecundity correlates with total length (r=0.75) and weight (r=0.71) of GFP. The total length of GFP was significantly associated with egg mass weight (r=0.74) in mesotrophic reservoirs compared to eutrophic reservoirs. Correlations between fecundity and body weight (r=0.70), fecundity and egg mass weight (r=0.76), egg mass weight and total length (r=0.69), and weight (r=0.72) were stronger in minor perennial reservoirs than in major and medium reservoirs. The present findings confirm that fecundity depends on the length, weight, and egg mass weight of ovigerous GFP, but not on the egg volume. The results align with the postulated hypothesis that the fecundity of ovigerous GFP varies with the trophic status and size of the reservoir.